EVALUATION OF BIOLOGICAL ASSETS AND PECULIARITIES OF FINDING THE FINANCIAL RESULT OF AGRICULTURAL ENTERPRISES OF THE REGION (Regional aspects of productive forces development of Ukraine, 2019)
The necessity of improving the methodology for evaluating agricultural products and additional biological assets with initial recognition, as well as reflection in the account of financial results of agricultural activity, is substantiated.